In situ construction of CoSe2@vertical-oriented graphene arrays as self-supporting electrodes for sodium-ion capacitors and electrocatalytic oxygen evolution. (June 2019) - Xia, Zhou; Sun, Hao; He, Xin; Sun, Zhongti; Lu, Chen; Li, Jie; Peng, Yang; Dou, Shixue; Sun, Jingyu; Liu, Zhongfan
Abstract: Transitional metal dichacogenides (TMDs) have stimulated an increasing research and technological attention due to their unique properties, holding great promise for emerging energy storage and conversion applications. However, tailorable and efficient synthesis of TMDs to garner the electrochemical and electrocatalytic performance of thus-derived electrodes has by far remained challenging. Herein we demonstrate a versatile synthetic strategy to in situ grow CoSe2 @vertically-oriented graphene (VG) hierarchical architecture on carbon fiber cloth (CC) via combined steps of plasma-enhanced chemical vapor deposition and wet chemistry. Such self-supporting and flexible CoSe2 @VG/CC arrays possess significant implications for pseudocapacitive Na storage and electrocatalytic O2 evolution (OER). When evaluated as an anode material for sodium-ion hybrid capacitors, full cells comprising a CoSe2 @VG/CC anode and AC cathode enable a favorable cyclic stability at 0.5 A g −1 for 1800 cycles in the potential range of 0.5–3.3 V, harvesting a high energy and power density of 116 Wh kg −1 and 7298 W kg −1 . In addition, CoSe2 @VG/CC array also exhibits an excellent OER performance with a low overpotential of 418 mV and Tafel slope of 82 mV dec −1 on a basis of experimental exploration and theoretical simulation. Graphical abstract: Image 1 Highlights: Self-supporting CoSe2 @VG/CC array was fabricated in-situ throughout combined steps of PECVD and wet chemistry. Thus-derived flexible array possessed implications for pseudocapacitive Na storage and electrocatalytic O2 evolution. The constructed Na-ion capacitors harvested a high energy and power density of 116 Wh kg −1 and 7298 W kg −1 . The electrocatalytic O2 evolution performances were thoroughly probed via experimental studies in combination with DFT simulations.